Заплатка - Носов Николай Николаевич (Мои любимые книжки, 2016)
Экземпляры: Ф22 (20161122) / Инвентарный номер: 53147 / Цена: 42.00 / Сис.шифр: Д / Авт.знак: Н 84 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6